PENGARUH LAYANAN KONSELING KELOMPOK TEKNIK COGNITIF BEHAVIOR THERAPY (CBT) TERHADAP KONFLIK INTERPERSONAL MAHASISWA PRODI BK DI UMN AL-WASHLIYAH MEDAN - Nursyadila Purba; Nur Asyah; Vinda Chairunnisa; Ika Sandra Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Interpersonal conflict is an ongoing conflict arising from incompatible differences in perspective between individuals. This study aims to determine the effect of group counseling services utilizing Cognitive Behavioral Therapy (CBT) techniques on the interpersonal conflict experienced by students in the Guidance and Counseling Study Program at UMN Al-Washliyah Medan. Group counseling based on the CBT approach plays a crucial role by emphasizing the interrelationship between thoughts, feelings, and behaviors, and by helping individuals identify and alter negative or irrational thought patterns that drive maladaptive behaviors. The study employs a quantitative approach using a pre-experimental